Product attributes affecting the substitutability of saiga horn drinks among young adult consumers in Singapore - Doughty, H; Lim, N; Carrasco, R; Milner-Gulland, EJ; Verissimo, D (Wiley, 2021)
Globally, illegal and unsustainable wildlife trade can drive biodiversity loss. Understanding which product attributes consumers consider when deciding between products of threatened species or alternatives, is key for conservation interventions. Labeled Discrete Choice Experiments (DCEs) are underutilized in wildlife trade literature but can aid this understanding. In labeled DCEs, the alternatives presented to respondents have specific names (e.g., paracetamol) as opposed to being generic bundles (e.g., option A). We used a labeled DCE to assess young adult preferences toward “cooling water” used to treat fever and heatiness (a traditional Chinese medicine state of illness) in Singapore. One popular cooling water contains saiga horn, made from Critically Endangered Saiga tatarica antelope. Data from 639 university-enrolled respondents were analyzed using latent class models. Middle- to high-income Chinese Singaporeans were the respondents most likely to choose saiga horn. Overall, however, respondents significantly preferred lower price products sold in nearby outlets—suggesting that for young adults in Singapore, saiga horn cooling water may be substitutable if its physical and financial availability is reduced.